THE RE-INDUSTRIALIZATION IN THE UNITED STATES AND THE EU - SERGEY ALEXEEVICH Pobyvaiev; SERGEY ALEXANDROVICH Tolkachev (Мир новой экономики, 2018)
The article is devoted to modern re-industrialization processes occurring in the two main centers of economic power: the US and the EU. These processes draw the attention of analysts, who tend to make far-reaching conclusions about the new stage of industrial development of the world post-industrial decline and the development of a paradigm shift. The purpose of the article is to establish whether this is the case. Based on the analysis and comparison of statistical data and expert estimations the authors conclude that, despite the development of re-industrialization process in the US and the EU, it is premature to talk about any qualitative change. In addition, the article notes that the process of re-industrialization in the United States and the EU are different in many respects: in the United States re-industrialization is mainly due to reshoring, in the EU it is mainly due to the EU programs and national programs. At the same time, the economic potential of the EU and the United States is so high that an increase in the rate of re-industrialization may change the ratio of economic power on the geopolitical level.